Carbon use efficiencies and allocation strategies in Prochlorococcus marinus strain PCC 9511 during nitrogen-limited growth - Felcmanová, Kristina; Lukeš, Martin; Kotabová, Eva; Lawrenz, Evelyn; Halsey, Kimberly H; Prášil, Ondřej (Photosynthesis research, 2017)
We studied cell properties including carbon allocation dynamics in the globally abundant and important cyanobacterium Prochlorococcus marinus strain PCC 9511 grown at three different growth rates in nitrogen-limited continuous cultures. With increasing nitrogen limitation, cellular divinyl chlorophyll a and the functional absorption cross section of Photosystem II decreased, although maximal photosynthetic efficiency of PSII remained unaltered across all N-limited growth rates. Chl-specific gross and net carbon primary production were also invariant with nutrient-limited growth rate, but only 20% of Chl-specific gross carbon primary production was retained in the biomass across all growth rates. In nitrogen-replete cells, 60% of the assimilated carbon was incorporated into the protein pool while only 30% was incorporated into carbohydrates. As N limitation increased, new carbon became evenly distributed between these two pools. While many of these physiological traits are similar to those measured in other algae, there are also distinct differences, particularly the lower overall efficiency of carbon utilization. The latter provides new information needed for understanding and estimating primary production, particularly in the nutrient-limited tropical oceans where P. marinus dominates phytoplankton community composition.
Keywords: Carbon allocation; Primary production; sinice; Nitrogen limitation; Carbon; Cyanobacteria; uhlík; Nitrogen; Prochlorococcus; dusík; Prochlorococcus marinus